Electroplating alkaline wastewater zero discharge method

Through an electroplating alkaline wastewater treatment method including pretreatment, flocculation and precipitation, filtration and evaporation crystallization, the problem that electroplating alkaline wastewater treatment in the prior art is difficult to achieve zero emissions, and efficient, economical and environmentally friendly wastewater treatment is achieved Effect.

CN119430578APending Publication Date: 2025-02-14YUYAO ADISHENG ELECTROPLATING TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411928831.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing electroplating alkaline wastewater treatment methods are difficult to achieve true zero emissions, and the treatment costs are high and the effect is unstable, which cannot meet the increasingly stringent environmental protection requirements.

Method used

A zero-discharge method for electroplating alkaline wastewater is adopted, including pretreatment, flocculation and precipitation, filtration and evaporation crystallization steps. Preliminary filtration through a screen, acid solution neutralization was added, lignin-modified polymeric iron sulfate and modified fly ash were added as flocculant in the flocculation reaction tank, ultrafiltration and nanofiltration, and finally evaporated in the MVR evaporator Crystallization treatment achieves zero emission of wastewater.

Benefits of technology

It realizes efficient separation and conversion of electroplating alkaline wastewater, achieves zero emissions, has low treatment costs and stable effects, and can meet strict environmental protection requirements.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a zero discharge method of electroplating alkaline wastewater, which comprises the following steps: preliminarily filtering the alkaline wastewater generated by electroplating by using a screen, and adding an acidic solution to adjust the pH value of the wastewater to 7-8; adding a flocculating agent which accounts for 3-5% of the mass of the wastewater, then stirring at the stirring speed of 150-250r / min for 20-30 minutes, and then introducing the wastewater into a sedimentation tank for sedimentation for 2-2.4 hours; then filtering through an ultrafiltration device and a nanofiltration device; feeding the filtered wastewater into an MVR (mechanical vapor recompression) evaporator for evaporative crystallization treatment, discharging crystalline salt in a crystallizer through a scraper conveyor, and condensing at the temperature of 40-50 DEG C to realize zero discharge of the wastewater. According to the zero discharge method for the electroplating alkaline wastewater, harmful substances in the electroplating alkaline wastewater are efficiently separated and converted, and finally zero discharge of the wastewater is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wastewater treatment, and in particular to a zero-discharge method for electroplating alkaline wastewater. Background Art

[0002] Electroplating process has a wide range of applications in industrial fields, such as automobile manufacturing, aerospace, electronic equipment, etc. However, the alkaline wastewater generated in the electroplating process contains a large amount of heavy metal ions, hydroxide ions and other harmful substances. If not properly treated, it will cause serious pollution to the environment.

[0003] Traditional electroplating alkaline wastewater treatment methods mainly include neutralization, precipitation, electrolysis, etc. However, these methods often produce a large amount of sludge and wastewater during the treatment process, making it difficult to achieve true zero discharge. In addition, the treatment cost is high, and the treatment effect is unstable, making it difficult to meet increasingly stringent environmental protection requirements.

[0004] In order to solve the problem of treating alkaline wastewater from electroplating, domestic and foreign scholars and engineers have conducted a lot of research and exploration in recent years. Among them, some new treatment methods such as membrane separation technology, biological treatment technology, and advanced oxidation technology have gradually emerged. However, these methods still have some problems in practical applications, such as low treatment efficiency, high operating costs, and complex operations, which limit their widespread application.

[0005] Therefore, developing an efficient, economical and environmentally friendly zero-discharge method for electroplating alkaline wastewater is of great significance for promoting the sustainable development of the electroplating industry and protecting the ecological environment. The present invention proposes an innovative zero-discharge method for electroplating alkaline wastewater, aiming to solve the problems existing in the prior art and realize the harmless treatment and resource utilization of electroplating alkaline wastewater. Summary of the invention

[0006] The purpose of the present invention is to provide a method for zero discharge of electroplating alkaline wastewater, which can efficiently separate and transform harmful substances in electroplating alkaline wastewater and ultimately achieve zero discharge of wastewater.

[0007] The present invention provides a zero-discharge method for electroplating alkaline wastewater, comprising the following steps:

[0008] (1) Pretreatment: After the alkaline wastewater generated by electroplating is initially filtered through a sieve with a mesh size of 0.1-0.2 mm, the pH value of the wastewater is adjusted to 7-8 by adding an acidic solution;

[0009] (2) Flocculation sedimentation: The wastewater is introduced into a flocculation reaction tank, and a flocculant is added at a rate of 3-5% relative to the mass of the wastewater, followed by stirring at a rate of 150-250 r / min. After stirring for 20-30 min, the wastewater is introduced into a sedimentation tank for sedimentation, and the sedimentation time is 2-2.4 h;

[0010] (3) Filtration: The wastewater treated in step (2) is filtered sequentially through an ultrafiltration device and a nanofiltration device;

[0011] (4) Evaporation and crystallization: The filtered wastewater is sent to the MVR evaporator for evaporation and crystallization treatment. The crystallized salt in the crystallizer is discharged through a scraper conveyor and condensed at a temperature of 40-50°C to achieve zero discharge of wastewater.

[0012] Furthermore, the acidic solution in step (1) is a sulfuric acid aqueous solution or a hydrochloric acid aqueous solution with a mass concentration of 8-10%.

[0013] Furthermore, the flocculant in step (2) comprises lignin-modified polyferric sulfate and modified fly ash in a weight ratio of (10-12): (4-5).

[0014] Furthermore, the preparation method of the lignin-modified polyferric sulfate includes: dissolving lignin in deionized water with a pH of 10, adding polyferric sulfate, stirring for 2-3 hours at a temperature of 64-66°C, adjusting the pH to neutral with sulfuric acid with a mass concentration of 6-8%, stirring for 40-60 minutes, and then drying at a temperature of 55-65°C.

[0015] Furthermore, the weight ratio of the lignin, deionized water and polyferric sulfate is (3-5): (28-32): (12-14).

[0016] Furthermore, the preparation method of the modified fly ash comprises: baking the fly ash at temperatures of 300° C., 400° C. and 500° C. respectively, adding a silane coupling agent γ-mercaptopropyltriethoxysilane after cooling and grinding for 30-40 minutes to obtain the modified fly ash.

[0017] Furthermore, the fly ash is baked at 300° C. for 30-40 min, baked at 400° C. for 50-60 min, and baked at 500° C. for 30-40 min.

[0018] Furthermore, the weight ratio of the fly ash and the silane coupling agent is (5-6): (50-55).

[0019] Furthermore, the ultrafiltration membrane flux of the ultrafiltration device in step (3) is 75-85L / (m 2 ·h), the nanofiltration membrane flux of the nanofiltration device is 45-55L / (m 2 h), the pressure during the filtration process is 0.2-0.4 MPa.

[0020] Furthermore, in step (4), the evaporation temperature is 85-95° C., and the evaporation pressure is 0.04-0.06 MPa.

[0021] The beneficial effects of the present invention are:

[0022] In the present invention, the electroplating alkaline wastewater is firstly filtered using a screen to remove large particle impurities and suspended matter in the wastewater, providing relatively clear wastewater for subsequent treatment, and then neutralizing the alkaline substances in the wastewater to make the wastewater close to neutral; a flocculant is added to the flocculation reaction tank for wastewater treatment, and the active ingredients in the lignin-modified polyferric sulfate and modified fly ash can form floccules with heavy metal ions, organic matter, etc. in the wastewater. During the stirring process, the flocculant fully reacts with the harmful substances in the wastewater to form larger floccules. After the stirring is completed, the wastewater is introduced into a sedimentation tank for precipitation. During the precipitation process, the floccules gradually settle to the bottom to form sludge, and the supernatant becomes relatively clear. The wastewater after the precipitation treatment is filtered by an ultrafiltration device and a nanofiltration device in turn. The ultrafiltration device can intercept macromolecular substances, colloids, bacteria, etc. in the wastewater, and the nanofiltration device can further remove small molecular organic matter, heavy metal ions, etc. in the wastewater. Through these two levels of filtration, the harmful substances in the wastewater are further removed. Finally, the filtered wastewater is sent to the MVR evaporator for evaporation and crystallization. Evaporation and crystallization is a process of evaporation that gradually changes an unsaturated solution into a saturated solution, and then gradually changes into a supersaturated solution. At this time, the solute will precipitate from the supersaturated solution. For harmful substances in electroplating wastewater, such as heavy metal ions, they will be concentrated during the evaporation and crystallization process and eventually precipitate in the form of crystals. At the same time, condensation is carried out. The condensed water can be reused or discharged, and finally zero discharge of wastewater is achieved.

[0023] In the present invention, lignin-modified polyferric sulfate and modified fly ash are used as compound flocculation materials, which can effectively omit the heavy metal treatment step, and can achieve adsorption of heavy metals during flocculation, thereby reducing the emission of metal ions.

[0024] The present invention utilizes lignin-modified polyferric sulfate to achieve flocculation of wastewater and adsorption of heavy metal ions; the addition of lignin allows the flocculant to form a polymer structure, which has stronger adsorption capacity and bridging effect, and can quickly form floccules with harmful substances in the wastewater. Functional groups such as hydroxyl and carboxyl in lignin can chemically react or physically adsorb with heavy metal ions, organic matter, etc. in the wastewater, thereby improving flocculation efficiency.

[0025] The present invention also uses the zoned temperature to pre-bake the fly ash, and then uses the silane coupling agent to grind and modify the fly ash; through the baking treatment, the specific surface area and porosity of the fly ash are significantly increased, providing more adsorption sites for it, and the addition of the silane coupling agent increases the types and number of functional groups on the surface of the fly ash, and these functional groups can react chemically or physically adsorb with harmful substances such as heavy metal ions in wastewater. In addition, the addition of the silane coupling agent also improves the chemical stability of the fly ash, so that it can maintain stable adsorption performance in a wider range of pH values ​​and temperatures.

[0026] In the present invention, fly ash is pre-treated by baking at 300°C for 30-40min, baking at 400°C for 50-60min, and baking at 500°C for 30-40min. During the baking process at different temperatures, the formation of a temperature gradient helps to gradually eliminate moisture, volatile substances and organic components in the fly ash. As the temperature gradually increases, the internal structure of the fly ash will also undergo gradual changes, including the maturation of the pore structure and the expansion of the specific surface area. The method of short baking at different temperatures can avoid the damage to the fly ash structure or the reduction of active sites that may be caused by long-term high-temperature treatment. Accurately controlling the baking time can improve the adsorption characteristics and stability of the fly ash. At the same time, baking at different temperatures helps to promote the development of the internal pore structure of the fly ash, increase the number of pores and the breadth of pore size distribution, thereby providing more adsorption sites and enhancing the adsorption capacity and adsorption speed of the fly ash.

[0027] In the present invention, fly ash is modified by using γ-mercaptopropyl triethoxysilane, which significantly improves its adsorption performance and dispersibility. The adsorption performance of fly ash modified by silane coupling agents KH550, KH560 and KH570 is better than that of fly ash modified by silane coupling agents KH550, KH560 and KH570. This is because the mercaptosilane coupling agent has a mercapto functional group, which can react with metal ions or metal oxides on the surface of inorganic materials to form a stable chemical bond. When the mercaptosilane coupling agent contacts fly ash, its siloxane part can be hydrolyzed to generate silanol groups (-Si-OH), and these silanol groups can react with hydroxyl groups (-OH) or other oxygen-containing functional groups on the surface of fly ash to form a covalent bond. At the same time, the mercapto functional group reacts with metal ions or metal oxides on the surface of fly ash to form a sulfur-metal bond. This dual chemical bonding greatly enhances the interfacial bonding force between fly ash and organic or inorganic materials. The chemical composition and physical properties of the fly ash surface have been changed by the modification of mercaptosilane coupling agent. On the one hand, the introduction of mercapto functional groups increases the polarity of the fly ash surface, making it easier to interact with polar solvents or polar substances; on the other hand, the long chain structure of the silane coupling agent helps to improve the dispersibility and fluidity of fly ash, making it easier to disperse evenly in the solution. Due to the strong binding ability of mercapto functional groups with metal ions or metal oxides, the modified fly ash has a higher adsorption capacity and faster adsorption rate for harmful substances such as heavy metal ions in wastewater. In addition, mercapto functional groups can also act as ligands to react with certain organic matter in wastewater, thereby further improving its adsorption performance. DETAILED DESCRIPTION

[0028] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] This embodiment provides a method for zero discharge of electroplating alkaline wastewater, the steps comprising:

[0031] (1) Pretreatment: After the alkaline wastewater generated by electroplating is initially filtered through a sieve with a mesh size of 0.1 mm, the pH value of the wastewater is adjusted to 7.5 by adding a 9% sulfuric acid aqueous solution or a hydrochloric acid aqueous solution;

[0032] (2) Flocculation sedimentation: The wastewater was introduced into a flocculation reaction tank, and a flocculant of 4% relative to the mass of the wastewater was added, followed by stirring at a stirring speed of 200 r / min. After stirring for 25 min, the wastewater was introduced into a sedimentation tank for sedimentation, and the sedimentation time was 2.2 h;

[0033] The flocculant includes lignin-modified polyferric sulfate and modified fly ash in a weight ratio of 11:4.5;

[0034] The preparation method of lignin modified polyferric sulfate comprises: dissolving lignin in deionized water with a pH value of 10, adding polyferric sulfate, stirring for 2.5 hours at a temperature of 65° C., adjusting the pH value to neutral with sulfuric acid with a mass concentration of 7%, stirring for 50 minutes, and then drying at a temperature of 60° C. to obtain the product; the weight ratio of lignin, deionized water and polyferric sulfate is 4:30:13;

[0035] The preparation method of the modified fly ash comprises: baking the fly ash at 300°C for 35 minutes, baking at 400°C for 55 minutes, and baking at 500°C for 35 minutes, respectively, adding a silane coupling agent γ-mercaptopropyltriethoxysilane after cooling, and grinding for 35 minutes to obtain the fly ash; the weight ratio of the fly ash to the silane coupling agent is 5.5:52.5;

[0036] (3) Filtration: The wastewater treated in step (2) is filtered in turn through an ultrafiltration device and a nanofiltration device; the ultrafiltration membrane flux of the ultrafiltration device is 80 L / (m 2 ·h), the nanofiltration membrane flux of the nanofiltration device is 50L / (m 2 h), the pressure during the filtration process is 0.3 MPa;

[0037] (4) Evaporation and crystallization: The filtered wastewater is sent to the MVR evaporator for evaporation and crystallization treatment. The evaporation temperature is 90°C and the evaporation pressure is 0.05MPa. The crystallized salt in the crystallizer is discharged through a scraper conveyor and condensed into water at a temperature of 45°C.

[0038] Example 2

[0039] This embodiment provides a method for zero discharge of electroplating alkaline wastewater, the steps comprising:

[0040] (1) Pretreatment: After the alkaline wastewater generated by electroplating is initially filtered through a sieve with a mesh size of 0.1 mm, the pH value of the wastewater is adjusted to 7 by adding an 8% mass concentration of sulfuric acid aqueous solution or hydrochloric acid aqueous solution;

[0041] (2) Flocculation sedimentation: The wastewater is introduced into a flocculation reaction tank, and a flocculant is added at a rate of 3% relative to the mass of the wastewater, followed by stirring at a rate of 150 r / min. After stirring for 20 min, the wastewater is introduced into a sedimentation tank for sedimentation, and the sedimentation time is 2 h.

[0042] The flocculant comprises lignin-modified polyferric sulfate and modified fly ash in a weight ratio of 10:4;

[0043] The preparation method of lignin modified polyferric sulfate comprises: dissolving lignin in deionized water with a pH value of 10, adding polyferric sulfate, stirring for 2 hours at a temperature of 64° C., adjusting the pH value to neutral with sulfuric acid with a mass concentration of 6%, stirring for 40 minutes, and then drying at a temperature of 55° C. to obtain the product; the weight ratio of lignin, deionized water and polyferric sulfate is 3:28:12;

[0044] The preparation method of the modified fly ash comprises: baking the fly ash at 300°C for 30 minutes, baking at 400°C for 50 minutes, and baking at 500°C for 30 minutes, respectively, adding a silane coupling agent γ-mercaptopropyltriethoxysilane after cooling, and grinding for 30 minutes to obtain the fly ash; the weight ratio of the fly ash to the silane coupling agent is 5:50;

[0045] (3) Filtration: The wastewater treated in step (2) is filtered in turn through an ultrafiltration device and a nanofiltration device; the ultrafiltration membrane flux of the ultrafiltration device is 75 L / (m 2 ·h), the nanofiltration membrane flux of the nanofiltration device is 45L / (m 2 h), the pressure during the filtration process is 0.2 MPa;

[0046] (4) Evaporation and crystallization: The filtered wastewater is sent to the MVR evaporator for evaporation and crystallization treatment. The evaporation temperature is 85°C and the evaporation pressure is 0.04MPa. The crystallized salt in the crystallizer is discharged through a scraper conveyor and condensed into water at a temperature of 40°C.

[0047] Example 3

[0048] This embodiment provides a method for zero discharge of electroplating alkaline wastewater, the steps comprising:

[0049] (1) Pretreatment: After the alkaline wastewater generated by electroplating is initially filtered through a sieve with a mesh size of 0.2 mm, the pH value of the wastewater is adjusted to 8 by adding a 10% mass concentration of sulfuric acid aqueous solution or hydrochloric acid aqueous solution;

[0050] (2) Flocculation sedimentation: The wastewater was introduced into a flocculation reaction tank, and a flocculant of 5% relative to the mass of the wastewater was added, followed by stirring at a stirring speed of 250 r / min. After stirring for 30 min, the wastewater was introduced into a sedimentation tank for sedimentation, and the sedimentation time was 2.4 h;

[0051] The flocculant comprises lignin-modified polyferric sulfate and modified fly ash in a weight ratio of 12:5;

[0052] The preparation method of lignin modified polyferric sulfate comprises: dissolving lignin in deionized water with a pH value of 10, adding polyferric sulfate, stirring for 3 hours at a temperature of 66°C, adjusting the pH value to neutral with sulfuric acid with a mass concentration of 8%, stirring for 60 minutes, and then drying at a temperature of 65°C to obtain the product; the weight ratio of lignin, deionized water and polyferric sulfate is 5:32:14;

[0053] The preparation method of the modified fly ash comprises: baking the fly ash at 300°C for 40 minutes, baking at 400°C for 60 minutes, and baking at 500°C for 40 minutes, respectively, adding a silane coupling agent γ-mercaptopropyltriethoxysilane after cooling, and grinding for 40 minutes to obtain the fly ash; the weight ratio of the fly ash to the silane coupling agent is 6:55;

[0054] (3) Filtration: The wastewater treated in step (2) is filtered in turn through an ultrafiltration device and a nanofiltration device; the ultrafiltration membrane flux of the ultrafiltration device is 85 L / (m 2 ·h), the nanofiltration membrane flux of the nanofiltration device is 55L / (m 2 h), the pressure during the filtration process is 0.4 MPa;

[0055] (4) Evaporation and crystallization: The filtered wastewater is sent to the MVR evaporator for evaporation and crystallization treatment. The evaporation temperature is 95°C and the evaporation pressure is 0.06MPa. The crystallized salt in the crystallizer is discharged through a scraper conveyor and condensed into water at a temperature of 50°C.

[0056] Example 4

[0057] This embodiment provides a method for zero discharge of electroplating alkaline wastewater, the steps comprising:

[0058] (1) Pretreatment: After the alkaline wastewater generated by electroplating is initially filtered through a sieve with a mesh size of 0.1 mm, the pH value of the wastewater is adjusted to 7 by adding a 10% mass concentration of sulfuric acid aqueous solution or hydrochloric acid aqueous solution;

[0059] (2) Flocculation sedimentation: The wastewater is introduced into a flocculation reaction tank, and a flocculant is added at a rate of 5% relative to the mass of the wastewater, followed by stirring at a rate of 150 r / min. After stirring for 30 min, the wastewater is introduced into a sedimentation tank for sedimentation, and the sedimentation time is 2 h.

[0060] The flocculant comprises lignin-modified polyferric sulfate and modified fly ash in a weight ratio of 12:4;

[0061] The preparation method of lignin modified polyferric sulfate comprises: dissolving lignin in deionized water with a pH value of 10, adding polyferric sulfate, stirring for 2 hours at a temperature of 66° C., adjusting the pH value to neutral with sulfuric acid with a mass concentration of 8%, stirring for 40 minutes, and then drying at a temperature of 65° C. to obtain the product; the weight ratio of lignin, deionized water and polyferric sulfate is 3:32:12;

[0062] The preparation method of the modified fly ash comprises: baking the fly ash at 300°C for 40 minutes, baking at 400°C for 50 minutes, and baking at 500°C for 40 minutes, respectively, adding a silane coupling agent γ-mercaptopropyltriethoxysilane after cooling, and grinding for 30 minutes to obtain the fly ash; the weight ratio of the fly ash to the silane coupling agent is 6:50;

[0063] (3) Filtration: The wastewater treated in step (2) is filtered in turn through an ultrafiltration device and a nanofiltration device; the ultrafiltration membrane flux of the ultrafiltration device is 85 L / (m 2 ·h), the nanofiltration membrane flux of the nanofiltration device is 45L / (m 2 h), the pressure during the filtration process is 0.4 MPa;

[0064] (4) Evaporation and crystallization: The filtered wastewater is sent to the MVR evaporator for evaporation and crystallization treatment. The evaporation temperature is 85°C and the evaporation pressure is 0.06MPa. The crystallized salt in the crystallizer is discharged through a scraper conveyor and condensed into water at a temperature of 40°C.

[0065] Comparative Example 1

[0066] This comparative example provides a method for zero discharge of electroplating alkaline wastewater, the steps comprising:

[0067] (1) Pretreatment: After the alkaline wastewater generated by electroplating is initially filtered through a sieve with a mesh size of 0.1 mm, the pH value of the wastewater is adjusted to 7.5 by adding a 9% sulfuric acid aqueous solution or a hydrochloric acid aqueous solution;

[0068] (2) Flocculation sedimentation: The wastewater was introduced into a flocculation reaction tank, and a flocculant of 4% relative to the mass of the wastewater was added, followed by stirring at a stirring speed of 200 r / min. After stirring for 25 min, the wastewater was introduced into a sedimentation tank for sedimentation, and the sedimentation time was 2.2 h;

[0069] The flocculant includes lignin-modified polyferric sulfate and modified fly ash in a weight ratio of 11:4.5;

[0070] The preparation method of lignin modified polyferric sulfate comprises: dissolving lignin in deionized water with a pH value of 10, adding polyferric sulfate, stirring for 2.5 hours at a temperature of 65° C., adjusting the pH value to neutral with sulfuric acid with a mass concentration of 7%, stirring for 50 minutes, and then drying at a temperature of 60° C. to obtain the product; the weight ratio of lignin, deionized water and polyferric sulfate is 4:30:13;

[0071] The preparation method of the modified fly ash comprises: baking the fly ash at 300°C for 35 minutes, baking at 400°C for 55 minutes, and baking at 500°C for 35 minutes, respectively, adding silane coupling agent γ-aminopropyltriethoxysilane after cooling, and grinding for 35 minutes to obtain the fly ash; the weight ratio of fly ash to silane coupling agent is 5.5:52.5;

[0072] (3) Filtration: The wastewater treated in step (2) is filtered in turn through an ultrafiltration device and a nanofiltration device; the ultrafiltration membrane flux of the ultrafiltration device is 80 L / (m 2 ·h), the nanofiltration membrane flux of the nanofiltration device is 50L / (m 2 h), the pressure during the filtration process is 0.3 MPa;

[0073] (4) Evaporation and crystallization: The filtered wastewater is sent to the MVR evaporator for evaporation and crystallization treatment. The evaporation temperature is 90°C and the evaporation pressure is 0.05MPa. The crystallized salt in the crystallizer is discharged through a scraper conveyor and condensed into water at a temperature of 45°C.

[0074] Comparative Example 2

[0075] This comparative example provides a method for zero discharge of electroplating alkaline wastewater, the steps comprising:

[0076] (1) Pretreatment: After the alkaline wastewater generated by electroplating is initially filtered through a sieve with a mesh size of 0.1 mm, the pH value of the wastewater is adjusted to 7.5 by adding a 9% sulfuric acid aqueous solution or a hydrochloric acid aqueous solution;

[0077] (2) Flocculation sedimentation: The wastewater was introduced into a flocculation reaction tank, and a flocculant of 4% relative to the mass of the wastewater was added, followed by stirring at a stirring speed of 200 r / min. After stirring for 25 min, the wastewater was introduced into a sedimentation tank for sedimentation, and the sedimentation time was 2.2 h;

[0078] The flocculant includes lignin-modified polyferric sulfate and modified fly ash in a weight ratio of 11:4.5;

[0079] The preparation method of lignin modified polyferric sulfate comprises: dissolving lignin in deionized water with a pH value of 10, adding polyferric sulfate, stirring for 2.5 hours at a temperature of 65° C., adjusting the pH value to neutral with sulfuric acid with a mass concentration of 7%, stirring for 50 minutes, and then drying at a temperature of 60° C. to obtain the product; the weight ratio of lignin, deionized water and polyferric sulfate is 4:30:13;

[0080] The preparation method of the modified fly ash comprises: baking the fly ash at 300°C for 35 minutes, baking at 400°C for 55 minutes, and baking at 500°C for 35 minutes, respectively, adding a silane coupling agent γ-glycidyloxypropyltrimethoxysilane after cooling, and grinding for 35 minutes to obtain the fly ash; the weight ratio of the fly ash to the silane coupling agent is 5.5:52.5;

[0081] (3) Filtration: The wastewater treated in step (2) is filtered in turn through an ultrafiltration device and a nanofiltration device; the ultrafiltration membrane flux of the ultrafiltration device is 80 L / (m 2 ·h), the nanofiltration membrane flux of the nanofiltration device is 50L / (m 2 h), the pressure during the filtration process is 0.3 MPa;

[0082] (4) Evaporation and crystallization: The filtered wastewater is sent to the MVR evaporator for evaporation and crystallization treatment. The evaporation temperature is 90°C and the evaporation pressure is 0.05MPa. The crystallized salt in the crystallizer is discharged through a scraper conveyor and condensed into water at a temperature of 45°C.

[0083] Comparative Example 3

[0084] This comparative example provides a method for zero discharge of electroplating alkaline wastewater, the steps comprising:

[0085] (1) Pretreatment: After the alkaline wastewater generated by electroplating is initially filtered through a sieve with a mesh size of 0.1 mm, the pH value of the wastewater is adjusted to 7.5 by adding a 9% sulfuric acid aqueous solution or a hydrochloric acid aqueous solution;

[0086] (2) Flocculation sedimentation: The wastewater was introduced into a flocculation reaction tank, and a flocculant of 4% relative to the mass of the wastewater was added, followed by stirring at a stirring speed of 200 r / min. After stirring for 25 min, the wastewater was introduced into a sedimentation tank for sedimentation, and the sedimentation time was 2.2 h;

[0087] The flocculant includes lignin-modified polyferric sulfate and modified fly ash in a weight ratio of 11:4.5;

[0088] The preparation method of lignin modified polyferric sulfate comprises: dissolving lignin in deionized water with a pH value of 10, adding polyferric sulfate, stirring for 2.5 hours at a temperature of 65° C., adjusting the pH value to neutral with sulfuric acid with a mass concentration of 7%, stirring for 50 minutes, and then drying at a temperature of 60° C. to obtain the product; the weight ratio of lignin, deionized water and polyferric sulfate is 4:30:13;

[0089] The preparation method of the modified fly ash comprises: baking the fly ash at 300°C for 35 minutes, baking at 400°C for 55 minutes, and baking at 500°C for 35 minutes, respectively, adding a silane coupling agent γ-methacryloxypropyltrimethoxysilane after cooling, and grinding for 35 minutes to obtain the fly ash; the weight ratio of the fly ash to the silane coupling agent is 5.5:52.5;

[0090] (3) Filtration: The wastewater treated in step (2) is filtered in turn through an ultrafiltration device and a nanofiltration device; the ultrafiltration membrane flux of the ultrafiltration device is 80 L / (m 2 ·h), the nanofiltration membrane flux of the nanofiltration device is 50L / (m 2 h), the pressure during the filtration process is 0.3 MPa;

[0091] (4) Evaporation and crystallization: The filtered wastewater is sent to the MVR evaporator for evaporation and crystallization treatment. The evaporation temperature is 90°C and the evaporation pressure is 0.05MPa. The crystallized salt in the crystallizer is discharged through a scraper conveyor and condensed into water at a temperature of 45°C.

[0092] Comparative Example 4

[0093] This comparative example provides a method for zero discharge of electroplating alkaline wastewater, the steps comprising:

[0094] (1) Pretreatment: After the alkaline wastewater generated by electroplating is initially filtered through a sieve with a mesh size of 0.1 mm, the pH value of the wastewater is adjusted to 7.5 by adding a 9% sulfuric acid aqueous solution or a hydrochloric acid aqueous solution;

[0095] (2) Flocculation sedimentation: The wastewater was introduced into a flocculation reaction tank, and a flocculant of 4% relative to the mass of the wastewater was added, followed by stirring at a stirring speed of 200 r / min. After stirring for 25 min, the wastewater was introduced into a sedimentation tank for sedimentation, and the sedimentation time was 2.2 h;

[0096] The flocculant includes lignin-modified polyaluminium sulfate and modified fly ash in a weight ratio of 11:4.5;

[0097] The preparation method of lignin modified polyaluminium sulfate comprises: dissolving lignin in deionized water with a pH value of 10, adding polyaluminium sulfate, stirring for 2.5 hours at a temperature of 65°C, adjusting the pH value to neutral with 7% sulfuric acid, stirring for 50 minutes, and then drying at a temperature of 60°C to obtain the product; the weight ratio of lignin, deionized water and polyaluminium sulfate is 4:30:13;

[0098] The preparation method of the modified fly ash comprises: baking the fly ash at 300°C for 35 minutes, baking at 400°C for 55 minutes, and baking at 500°C for 35 minutes, respectively, adding a silane coupling agent γ-mercaptopropyltriethoxysilane after cooling, and grinding for 35 minutes to obtain the fly ash; the weight ratio of the fly ash to the silane coupling agent is 5.5:52.5;

[0099] (3) Filtration: The wastewater treated in step (2) is filtered in turn through an ultrafiltration device and a nanofiltration device; the ultrafiltration membrane flux of the ultrafiltration device is 80 L / (m 2 ·h), the nanofiltration membrane flux of the nanofiltration device is 50L / (m 2 h), the pressure during the filtration process is 0.3 MPa;

[0100] (4) Evaporation and crystallization: The filtered wastewater is sent to the MVR evaporator for evaporation and crystallization treatment. The evaporation temperature is 90°C and the evaporation pressure is 0.05MPa. The crystallized salt in the crystallizer is discharged through a scraper conveyor and condensed into water at a temperature of 45°C.

[0101] Comparative Example 5

[0102] This comparative example provides a method for zero discharge of electroplating alkaline wastewater, the steps comprising:

[0103] (1) Pretreatment: After the alkaline wastewater generated by electroplating is initially filtered through a sieve with a mesh size of 0.1 mm, the pH value of the wastewater is adjusted to 7.5 by adding a 9% sulfuric acid aqueous solution or a hydrochloric acid aqueous solution;

[0104] (2) Flocculation sedimentation: The wastewater was introduced into a flocculation reaction tank, and a flocculant of 4% relative to the mass of the wastewater was added, followed by stirring at a stirring speed of 200 r / min. After stirring for 25 min, the wastewater was introduced into a sedimentation tank for sedimentation, and the sedimentation time was 2.2 h;

[0105] The flocculant includes lignin-modified polyaluminium chloride and modified fly ash in a weight ratio of 11:4.5;

[0106] The preparation method of lignin modified polyaluminium chloride comprises: dissolving lignin in deionized water with a pH value of 10, adding polyaluminium chloride, stirring for 2.5 hours at a temperature of 65°C, adjusting the pH value to neutral with sulfuric acid with a mass concentration of 7%, stirring for 50 minutes, and then drying at a temperature of 60°C to obtain the product; the weight ratio of lignin, deionized water and polyaluminium chloride is 4:30:13;

[0107] The preparation method of the modified fly ash comprises: baking the fly ash at 300°C for 35 minutes, baking at 400°C for 55 minutes, and baking at 500°C for 35 minutes, respectively, adding a silane coupling agent γ-mercaptopropyltriethoxysilane after cooling, and grinding for 35 minutes to obtain the fly ash; the weight ratio of the fly ash to the silane coupling agent is 5.5:52.5;

[0108] (3) Filtration: The wastewater treated in step (2) is filtered in turn through an ultrafiltration device and a nanofiltration device; the ultrafiltration membrane flux of the ultrafiltration device is 80 L / (m 2 ·h), the nanofiltration membrane flux of the nanofiltration device is 50L / (m 2 h), the pressure during the filtration process is 0.3 MPa;

[0109] (4) Evaporation and crystallization: The filtered wastewater is sent to the MVR evaporator for evaporation and crystallization treatment. The evaporation temperature is 90°C and the evaporation pressure is 0.05MPa. The crystallized salt in the crystallizer is discharged through a scraper conveyor and condensed into water at a temperature of 45°C.

[0110] Comparative Example 6

[0111] This comparative example provides a method for zero discharge of electroplating alkaline wastewater, the steps comprising:

[0112] (1) Pretreatment: After the alkaline wastewater generated by electroplating is initially filtered through a sieve with a mesh size of 0.1 mm, the pH value of the wastewater is adjusted to 7.5 by adding a 9% sulfuric acid aqueous solution or a hydrochloric acid aqueous solution;

[0113] (2) Flocculation sedimentation: The wastewater was introduced into a flocculation reaction tank, and a flocculant of 4% relative to the mass of the wastewater was added, followed by stirring at a stirring speed of 200 r / min. After stirring for 25 min, the wastewater was introduced into a sedimentation tank for sedimentation, and the sedimentation time was 2.2 h;

[0114] The flocculant includes lignin-modified polyferric chloride and modified fly ash in a weight ratio of 11:4.5;

[0115] The preparation method of lignin modified polyferric chloride comprises: dissolving lignin in deionized water with a pH value of 10, adding polyferric chloride, stirring for 2.5 hours at a temperature of 65° C., adjusting the pH value to neutral with sulfuric acid with a mass concentration of 7%, stirring for 50 minutes, and then drying at a temperature of 60° C. to obtain the product; the weight ratio of lignin, deionized water and polyferric chloride is 4:30:13;

[0116] The preparation method of the modified fly ash comprises: baking the fly ash at 300°C for 35 minutes, baking at 400°C for 55 minutes, and baking at 500°C for 35 minutes, respectively, adding a silane coupling agent γ-mercaptopropyltriethoxysilane after cooling, and grinding for 35 minutes to obtain the fly ash; the weight ratio of the fly ash to the silane coupling agent is 5.5:52.5;

[0117] (3) Filtration: The wastewater treated in step (2) is filtered in turn through an ultrafiltration device and a nanofiltration device; the ultrafiltration membrane flux of the ultrafiltration device is 80 L / (m 2 ·h), the nanofiltration membrane flux of the nanofiltration device is 50L / (m 2 h), the pressure during the filtration process is 0.3 MPa;

[0118] (4) Evaporation and crystallization: The filtered wastewater is sent to the MVR evaporator for evaporation and crystallization treatment. The evaporation temperature is 90°C and the evaporation pressure is 0.05MPa. The crystallized salt in the crystallizer is discharged through a scraper conveyor and condensed into water at a temperature of 45°C.

[0119] Comparative Example 7

[0120] This comparative example provides a method for zero discharge of electroplating alkaline wastewater, the steps comprising:

[0121] (1) Pretreatment: After the alkaline wastewater generated by electroplating is initially filtered through a sieve with a mesh size of 0.1 mm, the pH value of the wastewater is adjusted to 7.5 by adding a 9% sulfuric acid aqueous solution or a hydrochloric acid aqueous solution;

[0122] (2) Flocculation sedimentation: The wastewater was introduced into a flocculation reaction tank, and a flocculant of 4% relative to the mass of the wastewater was added, followed by stirring at a stirring speed of 200 r / min. After stirring for 25 min, the wastewater was introduced into a sedimentation tank for sedimentation, and the sedimentation time was 2.2 h;

[0123] The flocculant comprises chitosan-modified polyferric sulfate and modified fly ash in a weight ratio of 11:4.5;

[0124] The preparation method of chitosan modified polyferric sulfate comprises: dissolving chitosan in deionized water with a pH value of 10, adding polyferric sulfate, stirring for 2.5 hours at a temperature of 65° C., adjusting the pH value to neutral with sulfuric acid with a mass concentration of 7%, stirring for 50 minutes, and then drying at a temperature of 60° C. to obtain the chitosan modified polyferric sulfate; the weight ratio of chitosan, deionized water and polyferric sulfate is 4:30:13;

[0125] The preparation method of the modified fly ash comprises: baking the fly ash at 300°C for 35 minutes, baking at 400°C for 55 minutes, and baking at 500°C for 35 minutes, respectively, adding a silane coupling agent γ-mercaptopropyltriethoxysilane after cooling, and grinding for 35 minutes to obtain the fly ash; the weight ratio of the fly ash to the silane coupling agent is 5.5:52.5;

[0126] (3) Filtration: The wastewater treated in step (2) is filtered in turn through an ultrafiltration device and a nanofiltration device; the ultrafiltration membrane flux of the ultrafiltration device is 80 L / (m 2 ·h), the nanofiltration membrane flux of the nanofiltration device is 50L / (m 2 h), the pressure during the filtration process is 0.3 MPa;

[0127] (4) Evaporation and crystallization: The filtered wastewater is sent to the MVR evaporator for evaporation and crystallization treatment. The evaporation temperature is 90°C and the evaporation pressure is 0.05MPa. The crystallized salt in the crystallizer is discharged through a scraper conveyor and condensed into water at a temperature of 45°C.

[0128] Comparative Example 8

[0129] This comparative example provides a method for zero discharge of electroplating alkaline wastewater, the steps comprising:

[0130] (1) Pretreatment: After the alkaline wastewater generated by electroplating is initially filtered through a sieve with a mesh size of 0.1 mm, the pH value of the wastewater is adjusted to 7.5 by adding a 9% sulfuric acid aqueous solution or a hydrochloric acid aqueous solution;

[0131] (2) Flocculation sedimentation: The wastewater was introduced into a flocculation reaction tank, and a flocculant of 4% relative to the mass of the wastewater was added, followed by stirring at a stirring speed of 200 r / min. After stirring for 25 min, the wastewater was introduced into a sedimentation tank for sedimentation, and the sedimentation time was 2.2 h;

[0132] The flocculant comprises polyferric sulfate and modified fly ash in a weight ratio of 11:4.5;

[0133] The preparation method of the modified fly ash comprises: baking the fly ash at 300°C for 35 minutes, baking at 400°C for 55 minutes, and baking at 500°C for 35 minutes, respectively, adding a silane coupling agent γ-mercaptopropyltriethoxysilane after cooling, and grinding for 35 minutes to obtain the fly ash; the weight ratio of the fly ash to the silane coupling agent is 5.5:52.5;

[0134] (3) Filtration: The wastewater treated in step (2) is filtered in turn through an ultrafiltration device and a nanofiltration device; the ultrafiltration membrane flux of the ultrafiltration device is 80 L / (m 2 ·h), the nanofiltration membrane flux of the nanofiltration device is 50L / (m 2 h), the pressure during the filtration process is 0.3 MPa;

[0135] (4) Evaporation and crystallization: The filtered wastewater is sent to the MVR evaporator for evaporation and crystallization treatment. The evaporation temperature is 90°C and the evaporation pressure is 0.05MPa. The crystallized salt in the crystallizer is discharged through a scraper conveyor and condensed into water at a temperature of 45°C.

[0136] Comparative Example 9

[0137] This comparative example provides a method for zero discharge of electroplating alkaline wastewater, the steps comprising:

[0138] (1) Pretreatment: After the alkaline wastewater generated by electroplating is initially filtered through a sieve with a mesh size of 0.1 mm, the pH value of the wastewater is adjusted to 7.5 by adding a 9% sulfuric acid aqueous solution or a hydrochloric acid aqueous solution;

[0139] (2) Flocculation sedimentation: The wastewater was introduced into a flocculation reaction tank, and a flocculant of 4% relative to the mass of the wastewater was added, followed by stirring at a stirring speed of 200 r / min. After stirring for 25 min, the wastewater was introduced into a sedimentation tank for sedimentation, and the sedimentation time was 2.2 h;

[0140] The flocculant includes lignin-modified polyferric sulfate and modified fly ash in a weight ratio of 11:4.5;

[0141] The preparation method of lignin modified polyferric sulfate comprises: dissolving lignin in deionized water with a pH value of 10, adding polyferric sulfate, stirring for 2.5 hours at a temperature of 65° C., adjusting the pH value to neutral with sulfuric acid with a mass concentration of 7%, stirring for 50 minutes, and then drying at a temperature of 60° C. to obtain the product; the weight ratio of lignin, deionized water and polyferric sulfate is 4:30:13;

[0142] The preparation method of the modified fly ash comprises: baking the fly ash at 400°C for 125 minutes, adding a silane coupling agent γ-mercaptopropyltriethoxysilane after cooling, and grinding for 35 minutes to obtain the fly ash; the weight ratio of the fly ash to the silane coupling agent is 5.5:52.5;

[0143] (3) Filtration: The wastewater treated in step (2) is filtered in turn through an ultrafiltration device and a nanofiltration device; the ultrafiltration membrane flux of the ultrafiltration device is 80 L / (m 2 ·h), the nanofiltration membrane flux of the nanofiltration device is 50L / (m 2 h), the pressure during the filtration process is 0.3 MPa;

[0144] (4) Evaporation and crystallization: The filtered wastewater is sent to the MVR evaporator for evaporation and crystallization treatment. The evaporation temperature is 90°C and the evaporation pressure is 0.05MPa. The crystallized salt in the crystallizer is discharged through a scraper conveyor and condensed into water at a temperature of 45°C.

[0145] Comparative Example 10

[0146] This comparative example provides a method for zero discharge of electroplating alkaline wastewater, the steps comprising:

[0147] (1) Pretreatment: After the alkaline wastewater generated by electroplating is initially filtered through a sieve with a mesh size of 0.1 mm, the pH value of the wastewater is adjusted to 7.5 by adding a 9% sulfuric acid aqueous solution or a hydrochloric acid aqueous solution;

[0148] (2) Flocculation sedimentation: The wastewater was introduced into a flocculation reaction tank, and a flocculant of 4% relative to the mass of the wastewater was added, followed by stirring at a stirring speed of 200 r / min. After stirring for 25 min, the wastewater was introduced into a sedimentation tank for sedimentation, and the sedimentation time was 2.2 h;

[0149] The flocculant includes lignin-modified polyferric sulfate and fly ash in a weight ratio of 11:4.5;

[0150] The preparation method of lignin modified polyferric sulfate comprises: dissolving lignin in deionized water with a pH value of 10, adding polyferric sulfate, stirring for 2.5 hours at a temperature of 65° C., adjusting the pH value to neutral with sulfuric acid with a mass concentration of 7%, stirring for 50 minutes, and then drying at a temperature of 60° C. to obtain the product; the weight ratio of lignin, deionized water and polyferric sulfate is 4:30:13;

[0151] (3) Filtration: The wastewater treated in step (2) is filtered in turn through an ultrafiltration device and a nanofiltration device; the ultrafiltration membrane flux of the ultrafiltration device is 80 L / (m 2 ·h), the nanofiltration membrane flux of the nanofiltration device is 50L / (m2 h), the pressure during the filtration process is 0.3 MPa;

[0152] (4) Evaporation and crystallization: The filtered wastewater is sent to the MVR evaporator for evaporation and crystallization treatment. The evaporation temperature is 90°C and the evaporation pressure is 0.05MPa. The crystallized salt in the crystallizer is discharged through a scraper conveyor and condensed into water at a temperature of 45°C.

[0153] The wastewater was treated by the treatment methods provided in the above Examples 1-4 and Comparative Examples 1-10. The water quality of the electroplating wastewater from a certain factory was as follows: pH value 12.5-13.7, suspended matter SS concentration of 80 mg / L, tin concentration of 143 mg / L, nickel concentration of 110 mg / L, copper concentration of 127 mg / L, aluminum concentration of 86 mg / L, zinc concentration of 45 mg / L, and chromium concentration of 38 mg / L.

[0154] After the wastewater treatment is completed, the condensed water is tested, and the results are shown in the following table:

[0155] Group Tin(mg / L) Nickel (mg / L) Copper (mg / L) Aluminum (mg / L) Zinc (mg / L) Chromium (mg / L) Example 1 0.09 0.03 0.17 0.12 0.01 0.04 Example 2 0.13 0.07 0.20 0.16 0.02 0.06 Example 3 0.10 0.05 0.19 0.14 0.01 0.06 Example 4 0.11 0.06 0.22 0.14 0.01 0.05 Comparative Example 1 0.87 1.25 1.10 0.62 0.25 0.54 Comparative Example 2 1.32 1.87 1.58 1.01 0.47 0.87 Comparative Example 3 2.16 3.22 2.86 1.35 0.68 1.55 Comparative Example 4 6.54 8.24 7.34 4.43 1.33 3.14 Comparative Example 5 8.66 10.52 9.65 6.37 1.88 3.68 Comparative Example 6 10.63 14.88 13.24 9.11 2.63 5.22 Comparative Example 7 12.57 13.04 12.89 11.02 3.54 5.72 Comparative Example 8 20.14 18.14 16.45 14.58 6.85 7.28 Comparative Example 9 10.75 11.21 13.54 8.56 4.45 6.62 Comparative Example 10 16.32 18.55 17.86 12.45 5.52 7.03

[0156] The above Examples 1-4 show that the pH of the condensed effluent from the electroplating wastewater treated by the method of the present invention is 6.8-7.4, the suspended matter concentration is 0.8-1.5 mg / L, the tin concentration is 0.09-0.13 mg / L, the nickel concentration is 0.03-0.07 mg / L, the copper concentration is 0.17-0.22 mg / L, the aluminum concentration is 0.12-0.16 mg / L, the zinc concentration is 0.01-0.02 mg / L, and the chromium concentration is 0.04-0.06 mg / L.

[0157] Finally, it should be noted that the above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents. All technical solutions and improvements that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A zero-discharge method for electroplating alkaline wastewater, characterized in that the steps include: (1) Pretreatment: After the alkaline wastewater generated by electroplating is initially filtered through a sieve with a mesh size of 0.1-0.2 mm, the pH value of the wastewater is adjusted to 7-8 by adding an acidic solution; (2) Flocculation sedimentation: The wastewater is introduced into a flocculation reaction tank, and a flocculant is added at a rate of 3-5% relative to the mass of the wastewater, followed by stirring at a rate of 150-250 r / min. After stirring for 20-30 min, the wastewater is introduced into a sedimentation tank for sedimentation, and the sedimentation time is 2-2.4 h; (3) Filtration: The wastewater treated in step (2) is filtered sequentially through an ultrafiltration device and a nanofiltration device; (4) Evaporation and crystallization: The filtered wastewater is sent to the MVR evaporator for evaporation and crystallization treatment. The crystallized salt in the crystallizer is discharged through a scraper conveyor and condensed at a temperature of 40-50°C to achieve zero discharge of wastewater.

2. A zero-discharge method for electroplating alkaline wastewater according to claim 1, characterized in that: The acidic solution in step (1) is a sulfuric acid aqueous solution or a hydrochloric acid aqueous solution with a mass concentration of 8-10%.

3. A zero-discharge method for electroplating alkaline wastewater according to claim 1, characterized in that: The flocculant in step (2) comprises lignin-modified polyferric sulfate and modified fly ash in a weight ratio of (10-12): (4-5).

4. A zero-discharge method for electroplating alkaline wastewater according to claim 3, characterized in that: The preparation method of the lignin-modified polyferric sulfate comprises: dissolving lignin in deionized water with a pH value of 10, adding polyferric sulfate, stirring for 2-3 hours at a temperature of 64-66° C., adjusting the pH value to neutral with sulfuric acid with a mass concentration of 6-8%, stirring for 40-60 minutes, and then drying at a temperature of 55-65° C. to obtain the product.

5. A zero-discharge method for electroplating alkaline wastewater according to claim 4, characterized in that: The weight ratio of the lignin, deionized water and polyferric sulfate is (3-5): (28-32): (12-14).

6. A zero-discharge method for electroplating alkaline wastewater according to claim 3, characterized in that: The preparation method of the modified fly ash comprises: baking the fly ash at 300° C., 400° C. and 500° C. respectively, adding silane coupling agent γ-mercaptopropyltriethoxysilane after cooling, and grinding for 30-40 minutes to obtain the fly ash.

7. A zero-discharge method for electroplating alkaline wastewater according to claim 6, characterized in that: The fly ash is baked at 300° C. for 30-40 minutes, at 400° C. for 50-60 minutes, and at 500° C. for 30-40 minutes.

8. A zero-discharge method for electroplating alkaline wastewater according to claim 6, characterized in that: The weight ratio of the fly ash to the silane coupling agent is (5-6): (50-55).

9. A zero-discharge method for electroplating alkaline wastewater according to claim 1, characterized in that: The ultrafiltration membrane flux of the ultrafiltration device in step (3) is 75-85L / (m 2 ·h), the nanofiltration membrane flux of the nanofiltration device is 45-55L / (m 2 h), the pressure during the filtration process is 0.2-0.4 MPa.

10. A zero-discharge method for electroplating alkaline wastewater according to claim 1, characterized in that: In the step (4), the evaporation temperature is 85-95° C., and the evaporation pressure is 0.04-0.06 MPa.

Citation Information

Patent Citations

  • Zero-discharge treatment method for electroplating wastewater

    CN106242143A

  • Preparation method of functionalized fly ash

    CN108889269A